2015
DOI: 10.1007/s10725-015-0099-x
|View full text |Cite
|
Sign up to set email alerts
|

Silicon nutrition and mycorrhizal inoculations improve growth, nutrient status, K+/Na+ ratio and yield of Cicer arietinum L. genotypes under salinity stress

Abstract: Salinity is a major abiotic stress that limits plant growth and productivity. Role of silicon (Si) nutrition and arbuscular mycorrhiza (AM) in mitigating salt stress has gained importance in recent years. Legumes are sensitive to salinity and are considered low Si-accumulators. AM have been reported to increase Si uptake in mycorrhizal plants. However, little is known about the alleviative role of Si and/ or AM in mitigating salt stress in Cicer arietinum L. (chickpea). Therefore, the present study was aimed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(61 citation statements)
references
References 66 publications
(89 reference statements)
6
42
1
1
Order By: Relevance
“…Specifically, salt stress decreased the SL, NL per plant, biomass (Figure 1), photosynthetic pigment synthesis, and gas exchange attributes in both tested genotypes (Figures 2-4). Moreover, the higher reduction in the SS cultivar indicated a more severe adverse effect of salinity on the SS cultivar, which is consistent with previous reports [41,42]. Recent studies in tomato [17], wheat [21], Hordeum vulgare [43], Carrizo citrange [44], Spartina alterniflora [45], Sorghum bicolor [46], and Brassica [34] showed that higher nitrogen supplementation can regulate the salinity tolerance and improve plant growth.…”
Section: Discussionsupporting
confidence: 90%
“…Specifically, salt stress decreased the SL, NL per plant, biomass (Figure 1), photosynthetic pigment synthesis, and gas exchange attributes in both tested genotypes (Figures 2-4). Moreover, the higher reduction in the SS cultivar indicated a more severe adverse effect of salinity on the SS cultivar, which is consistent with previous reports [41,42]. Recent studies in tomato [17], wheat [21], Hordeum vulgare [43], Carrizo citrange [44], Spartina alterniflora [45], Sorghum bicolor [46], and Brassica [34] showed that higher nitrogen supplementation can regulate the salinity tolerance and improve plant growth.…”
Section: Discussionsupporting
confidence: 90%
“…Also, Si had a signiicant effect on plant dry weight, so that, with using Si, plant dry weight improved under salt stress (Table 2). Several studies have reported growth and plant biomass increase in Si application conditions, which is attributed to increased photosynthetic pigment concentrations and improved photosynthetic system (2,22). In our present study, plant exposed to Si application resulted in an improvement of photosynthetic pigments content under salinity stress and non-stress conditions.…”
Section: Growth Parameterssupporting
confidence: 63%
“…Also, the results showed that Si increased the content of photosynthetic pigments under salt stress (Table 2). In several studies, Si application has been reported to increase the concentration of pigments (2,22).…”
Section: Photosynthetic Pigmentsmentioning
confidence: 99%
“…The authors suggested that the enhanced growth and salinity tolerance might be due to the synergistic effect of bacterial inoculants and Si fertilizer. Earlier, Garg and Bhandari (2016a) documented that combined application of arbuscular mycorrhiza and Si complemented each other to augment salinity-affected Cicer arietinum growth and biomass production.…”
Section: Discussionmentioning
confidence: 99%